Stereotactic body radiotherapy for oligo-metastatic liver disease: influence of pre-treatment chemotherapy and histology on local tumor control - Klement, Rainer J.; Boda-Heggemann, Judit; Habermehl, Daniel (Radiotherapy and oncology, 2017)
Introduction - Stereotactic body radiation therapy (SBRT) is applied in the oligometastatic setting to treat liver metastases. However, factors influencing tumor control probability (TCP) other than radiation dose have not been thoroughly investigated. Here we set out to investigate such factors with a focus on the influence of histology and chemotherapy prior to SBRT using a large multi-center database from the German Society of Radiation Oncology. - Methods - 452 SBRT treatments in 363 patients were analyzed after collection of patient, tumor and treatment data in a multi-center database. Histology was considered through random effects in semi-parametric and parametric frailty models. Dose prescriptions were parametrized by conversion to the maximum biologically effective dose using alpha/beta of 10Gy (BEDmax). - Results - After adjusting for histology, BEDmax was the strongest predictor of TCP. Larger PTV volumes, chemotherapy prior to SBRT and simple motion management techniques predicted significantly lower TCP. The model predicted a BED of 209±67Gy10 necessary for 90% TCP at 2years with no prior chemotherapy, but 286±78Gy10 when chemotherapy had been given. Breast cancer metastases were significantly more responsive to SBRT compared to other histologies with 90% TCP at 2years achievable with BEDmax of 157±80Gy10 or 80±62Gy10 with and without prior chemotherapy, respectively. - Conclusions - Besides dose, histology and pretreatment chemotherapy were important factors influencing local TCP in this large cohort of liver metastases. After adjusting for prior chemotherapy, our data add to the emerging evidence that breast cancer metastases do respond better to hypofractionated SBRT compared to other histologies.
Gesehen am 29.10.2018